Inside debt compensation and its effect on corporate financial policy choices - Kanelis, Dimitrios (2017)
This dissertation examines the effects of inside debt compensation on managerial risk-seeking behaviour. Extant literature argues that besides equity and cash, managers are also compensated with debt-like instruments such as deferred compensation and pensions. These compensation components are typically unfunded and unsecured and expose the CEO to default risk similar to that faced by external debtholders (Edmans and Liu, 2011). As a result, managers with large inside debt holdings are expected to display lower financial risk tolerance (Cassel et al., 2012). Motivated by this argument, I first examine the effects of CEO inside debt compensation on corporate financial policy choices. I document a negative association between inside debt holdings and firm book leverage and a positive relationship between CEO inside debt holdings and firm solvency. Subsequently, I examine whether women, who are perceived to possess a risk profile similar to a manager with significant inside debt holdings receive similar inside debt compensation to men. However, I document no evidence of a difference in the inside debt compensation between genders.